Evaluating Representations of Mental Health in Young Adult Fiction: The Case of Stephen Chbosky’s The Perks of Being a Wallflower (ENTHYMEMA, 2016)
This article examines representations of mental health in young adult (YA) litearature, taking up Stephen Chbosky’s The Perks of Being a Wallflower (1999) as its case study. Paying attention to the affordances of the genre of “teen sick-lit,” I connect such YA literature to the broader field of narrative medicine and consider what can be gained from this relationship. After a careful analysis of Chbosky’s novel, I conclude with a set of criteria that serve as markers of YA texts that productively convey mental health experiences. Although my focus here is on mental illness representations, my criteria and textual analysis can be extended to narratives that focus on other illness and diseases, as well.